Cataloguer Acceptance on Cataloguing Module in Open-Source Integrated Library System in Academic Library in Malaysia - Sarif Abdullah, Sharifah Nur Amirah; Md Nor, Nor Saadah (University of Idaho Library, 2021)
This paper aims to identify the acceptance of cataloguers on cataloguing modules in the Open-Source Integrated Library System in an academic library in Malaysia. The research design adopted for this study is descriptive research surveys. This study involved cataloguers in the academic university library in Malaysia that have used Koha as their open-source software since 2013. The survey used an online questionnaire distributed via email to all cataloguers in the selected libraries. The questionnaire comprises questions related to acceptance of module features and module usability on the cataloguing module. The 5-point Likert scale is used to measure the cataloguer acceptance of the cataloguing module, and the data were analysed using SPSS. The findings conclude that the majority of the cataloguers in academic libraries in Malaysia use open-source integrated library system similar to this study, Koha, and have entirely accepted the use of cataloguing module in terms of usability and features as the majority of the data reported on agreement of the user compared to a minority of disagreement. The findings of this study will encourage other researchers to do other studies on the usability of other modules in the open-source system that might improve the acceptance of open-source software.